Evaluation of Radiological Health Risks in Popularly Consumed Brands of Sachet Water in Nigeria - Aladeniyi, Kehinde; Olowookere, Christopher Jimoh; Khandaker, Mayeen Uddin; Alsufyani, Sultan J. (Frontiers in Public Health, 2022)
Radiological investigation of 35 brands of most popularly used sachet drinking water in Ondo state, Nigeria has been carried out using spectrometric method with the aim of evaluating the associated health risks to the members of the public. Activity concentrations of the investigated radionuclides 40K, 226R and 228Ra were in the range of 16.35±4.10 to 199.94 ± 38.40 Bq L-1 with arithmetic mean (AM) of 66.22 ± 54.99 Bq L-1, from 1.35± 0.79 to 17.06 ± 5.13 Bq L-1 with an AM of 6.88 ± 3.66 Bq L-1, from 1.95 ± 0.08 to 17.22 ± 3.87 Bq L-1 with an AM of 9.49 ± 4.98 Bq L-1 respectively. The determined annual effective doses and the corresponding excess lifetime cancer risks due to 226Ra and 228Ra were found to exceed the acceptable limits of 0.1mSv y-1 and 10-3 respectively, suggested the World Health Organization (WHO). This implies a non-negligible carcinogenic health hazard due to the intake of the surveyed drinking water especially for the lactating babies (0-1) y and the teenagers (12-17) y. The data from this research may form an invaluable component of radiometric values of the database in Nigeria as well as the world for setting up guidelines and control policies of the use of sachet water.